Climate and the Nephrologist: The Intersection of Climate Change, Kidney Disease, and Clinical Care. Issue 3 (1st March 2023) - Young, Sarah E.; Khoshnaw, Laveen J.; Johnson, Richard J.
Abstract : Climate change is upon us, and it will have a major effect on both kidney disease and the nephrology practice. But the converse is also true: our treatment of kidney disease has an effect on the climate. Much attention has focused on how rising temperatures can lead to acute and CKD and health exacerbations in patients with established kidney disease. Climate change is also associated with rising air pollution from wildfires and industrial wastes and infectious diseases associated with flooding and changing habitats, all of which heighten the risk of acute and CKD. Less well recognized or understood are the ways nephrology practices, in turn, contribute to still more climate change. Hemodialysis, although lifesaving, can be associated with marked water usage (up to 600 L per dialysis session), energy usage (with one 4-hour session averaging as much as one fifth of the total energy consumed by a household per day), and large clinical wastes (with hemodialysis accounting for one third of total clinical medicine–associated waste). Of note, >90% of dialysis occurs in highly affluent countries, whereas dialysis is much less available in the poorer countries where climate change is having the highest effect on kidney disease. We conclude that not only do nephrologists need to prepare for the rise in climate-associated kidney disease, they must also urgently develop more climate-friendly methods of managing patients with kidney disease.